Content of some mineral elements in eggs from farms and free range - Stibilj, V; Terčič, Dušan; Holcman, Antonija (Acta Agraria Kaposváriensis, 2002)
The aim of our work was to investigate the relationship between different laying hens housing systems and content of some minerals in their eggs. Samples of eggs were collected from four commercial farms with intensive rearing systems (cage and deep litter eggs) and from four family farms with extensive rearing system (village hens -free range eggs). From each farm two samples, each consisted of three eggs, were randomly taken on a bi-weekly basis. Composited samples from three whites and three yolks respectively were formed in order to determine the minerals content. Exception was one family farm where ten eggs represented a sample. So 24 samples were collected from commercial farms and 24 from family farms. For the potassium, sodium, magnesium, calcium and zinc, the analysis was performed with atomic absorption spectrometry after dry ashing at 520 Â°C and dissolving in HCl acid. Phosphorus was analysed by spectrophotometer. The accuracy of the methods was validated by analysing the standard reference materials (SRM) of whole egg powder SRM 8415. Different housing systems had statistically significant effect (P<0.05) on potassium and magnesium levels in whites and yolks. Significant differences (P<0.05) between intensive and extensive rearing systems were also observed for sodium content in whites and for phosporus and zinc content in yolks. Levels of calcium did not statistically differ between the groups and were generally consistent. Concentrations of Zn in whites as well as in yolks were low and did not exceed of the maximum permitted concentration.